Micro-foundations as a grounding for readiness-for change in knowledge sharing initiatives. (17th November 2021) - Samara, Khalid; Serhan, Omar Al
While many organisations are often engaged in conventional change practices that usually involve top-down strategies for creating change, knowledge sharing initiatives differ where most of the complex processes are handled at the human-level. Therefore, knowledge sharing initiatives present a unique type of conundrum where there is a need to closely interconnect human behaviours and the person's readiness to identify the most effective approaches to achieve change. This paper investigates the individual level readiness-for change by studying organisational knowledge sharing initiatives from a micro-foundational perspective. These issues have been largely missing in the knowledge sharing literature which is integral to understanding of how to manage individuals at the micro-level who are experiencing a behavioural change as result of knowledge sharing initiatives. In this study an inductive grounded theory approach is being used to analyse the individuals' level experiences and origins of various influential factors supporting or inhibiting their readiness during knowledge sharing initiatives. The results indicate that asymmetries in communication and lack of awareness to knowledge sharing initiatives are fundamentally constructs akin to micro-level behaviours that have obvious effects on the individuals' readiness-for change.